Application of informative textural Law’s masks methods for processing space images - Moldir Yessenova; Gulzira Abdikerimova; Gulden Murzabekova; Kakabayev Nurbol; Natalya Glazyrina; Saltanat Adikanova; Nurgul Uzakkyzy; Zhanna B. Sadirmekova; Rozamgul Niyazova (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Image processing systems are currently used to solve many applied problems. The article is devoted to the identification of negative factors affecting the growth of grain in different periods of harvesting, using a program implemented in the MATLAB software environment, based on aerial photographs. The program is based on the Law’s textural mask method and successive clustering. This paper presents the algorithm of the program and shows the results of image processing by highlighting the uniformity of the image. To solve the problem, the spectral luminance coefficient (SBC), normalized difference vegetation index (NDVI), Law’s textural mask method, and clustering are used. This approach is general and has great potential for identifying objects and territories with different boundary properties on controlled aerial photographs using groups of images of the same surface taken at different vegetation periods. That is, the applicability of sets of Laws texture masks with original image enhancement for the analysis of experimental data on the identification of pest outbreaks is being investigated.